Desenvolvimento e construção de aparato experimental para caracterização da camada limite térmica laminar com base em modelagem via GITT - Lima, Fábio Araújo de (2019)
The present work aims to solve the mathematical model for characterization of the laminar thermal boundary layer using GITT (Generalized Integral Transform Technique) and with the results obtained from the modeling, to develop and build an experimental apparatus able to perform this characterization.A thermal boundary layer corresponds to a variation of the temperature field that occurs in a region near the wall of a solid body when it is exposed to fluid flow at a different temperature from its own. Studying it is important for many industrial applications, such as cooling system design for electronic components, solar energy capture, geothermal reservoirs, and advanced oil recovery The simulation results presented will be confronted with the results existing in the specialized literature. Currently, the techniques used to verify the thermal boundary layer apply invasive methods. The prototype developed to characterize the thermal boundary layer will be built based on a non-invasive method from the electromagnetic field model of a capacitive sensor. This sensor consists of two semi-cylindrical copper plates in opposite positions of a borosilicate glass tube. The liquid that fills the interior of the circular tube together with the borosilicate glass tube becomes the dielectric of the capacitor made up of the plates, making the sensor's response vary according to the characteristics of the liquid that is present inside the tube. Thermoelectric modules for liquid cooling in the tube and PT-1000 sensors were used to check the temperature that was controlled by PID controllers (Proportional, Integral and Derivative) tuned using the Ziegler-Nichols technique.